A platform for constructing, evaluating, and screening bioconjugates on the yeast surface. Issue 11 (22nd October 2016) - Van Deventer, James A.; Le, Doris N.; Zhao, Jessie; Kehoe, Haixing P.; Kelly, Ryan L.
Abstract: The combination of protein display technologies and noncanonical amino acids (ncAAs) offers unprecedented opportunities for the high throughput discovery and characterization of molecules suitable for addressing fundamental and applied problems in biological systems. Here we demonstrate that ncAA-compatible yeast display facilitates evaluations of conjugation chemistry and stability that would be challenging or impossible to perform with existing mRNA, phage, or E. coli platforms. Our approach enables site-specific introduction of ncAAs into displayed proteins, robust modification at azide-containing residues, and quantitative evaluation of conjugates directly on the yeast surface. Moreover, screening allows for the selective enrichment of chemically modified constructs while maintaining a genotype–phenotype linkage with encoded azide functionalities. Thus, this platform is suitable for the high throughput characterization and screening of libraries of chemically modified polypeptides for therapeutic lead discovery and other biological applications.